PRE-SEASON - Dzikic, Aleksandar; Mihajlovic, Filip (Sport- és Egészségtudományi füzetek, 2025)
Coach Džikić and Coach Mihajlović reviewed their experienc-es during Hapoel’s previous two preseasons in Jerusalem. Coaches’ primary job is to maximize players’ strengths or abilities and hide their weaknesses. As head coach I want to surround myself with people who are sharing my beliefs and ambition. Team chemistry is the sum of your private interest that you are ready to give up in order the team to achieve it’s goals.